Розроблення методів і засобів діагностики з підвищенням надійності екстракційного обладнання - Люлька, Дмитро Миколайович; Серьогін, Олександр Олександрович; Ізволенський, Ігор Євгенович; Мащенко, Олег Анатолійович; Чорний, Юрій Аркадійович (My University, 2023)
У статті наведено результати аналітичних та експериментальних досліджень напруженого стану транспортної системи колонного дифузійного апарата. Розвиток інформаційних систем ранньої діагностики дає змогу забезпечити раціональне управління та керування обладнанням, яке працює в критичних умовах, що забезпечує його надійну експлуатацію протягом сезону цукроваріння. Впровадження методики експериментального визначення пульсуючих навантажень, що діють на транспортні лопаті при експлуатації дифузійних апаратів, включаючи перехідні та критичні режими їх роботи, та отриманих на її основі результатів розрахунків, надасть можливість удосконалити конструкції транспортних систем екстракторів

The article presents the results of analytical and experimental studies of the stressed state of the transport system of the column diffusion apparatus. It is known that the development of the sugar industry in Ukraine is accompanied by an increase in the capacity of sugar factories. As a consequence, there is an emergence of a critical mechanical load on the working bodies of the basic equipment, including the transport system of the diffusion apparatus. Understanding the complex mechanical problems that arise during sugar production will allow us to propose measures that need to be taken to reduce the stresses in the main working organs of the transport systems of column extractors. An analytical review of modern methods and means of early diagnosis will allow us to find ways to reduce the negative impact and propose methods for effective distribution of voltages in critical parts of equipment elements. The development of information systems for early diagnosis facilitates the rational operation of equipment in critical conditions, ensuring its reliability during the sugar production season. It has been determined that efficient and reliable operation of extractors requires adherence to specific technological modes. Critical for the extraction process is the diagnosis and mixing of the solid phase. Mixing is necessary to restore the elastic properties of the mixture and improve the hydrodynamic environment in the column, but the intensity of mixing must be within specified, reasonable limits. Excessive mixing is detrimental, resulting in additional grinding of the chips and deterioration of the hydrodynamic properties of the sap mixture. Simultaneously, the study found that the shape of the blade can create a hydrodynamic mass, intensifying mass transfer processes in the apparatus. This allows us to determine scientifically based directions for improving the design of transport systems of extractors
Keywords: екстрактор; діагностика; надійність; напруження; тензодатчик; extractor; diagnosis; reliability; tension; strain gauge; кафедра технологічного обладнання та комп’ютерних технологій проектування; кафедра електропостачання і енергоменеджменту